Electronic structure of YbNiX3 (X =Si, Ge) studied by hard X‐ray photoemission spectroscopy. Issue 6 (14th April 2015) - Sato, Hitoshi; Utsumi, Yuki; Kodama, Junichi; Nagata, Heisuke; Avila, Marcos A.; Ribeiro, Raquel A.; Umeo, Kazunori; Takabatake, Toshiro; Mimura, Kojiro; Motonami, Satoru; Anzai, Hiroaki; Ueda, Shigenori; et al.
Abstract lectronic structure of the Kondo lattices YbNiX3 (X =Si, Ge) has been investigated by means of hard x‐ray photoemission spectroscopy (HAXPES) with hν = 5.95 keV. From the Yb 3d HAXPES spectra, the Yb valence in YbNiSi3 is estimated to be ∼ 2.92, which is almost temperature‐independent. On the other hand, the valence in YbNiGe3 is estimated to be 2.48 at 300 K, showing significant valence fluctuation, and gradually decreases to 2.41 at 20 K on cooling. The Ni 2p3/2 and Yb3+ 4f peaks exhibit opposite energy shifts amounting to ∼ 0.6 eV between YbNiSi3 and YbNiGe3. We propose a simple model for the electronic structure of YbNiX3 based on the HAXPES results. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)